FOLK BELIEFS IN PARAPSYCHOLOGICAL TREATMENT - Hakimova, Nubar Mursal kizi (International Journal of Psychosocial Rehabilitation, 2020)
As the folk medicine is generally an integral part of the daily life and the life of people its practical significance investigation, the investigation of this extremely complex system as a whole performed with different rites is important. The investigation of profession of a quack doctor and its some content parts such as the profession of a bone-setter, dislocation of some parts in body (“sinigchilig”) considering as a product of the initial stages of the development of social life in human history systematically comparative form with medicine of other Turkish and Eastern peoples attains the special importance in understanding of physician profession more easily which has the scientific-practical importance. The profession of a quack doctor formed in ancient times, as well as the profession of physician being the product of the after Islamic art period, no doubt, the role of rich materials collected during the scientific expeditions of folklore and ethnography is very valuable. The role of information about medicine saved in medieval manuscripts, as well as in works by our classical writers is very matchless, too. It is also noticed that the different elements being the base of folk medicine which is the leading content part of common Turkish material and spiritual value system, including the rites and witchcrafts, especially in further development levels of folk knowledge system to different folklore genres, the scientific investigations in Middle Ages, at the same time in the works by our classics have been thrown.